Comparative effects of traditional and integrated pelvic floor exercise in treating women with pelvic floor dysfunction- a single blinded quasi experimental study. - G.DEEPTHI; S.PRATHAP; HEPZIBAH KIRUBAIMANI; LAVANYA PRATHAP; P.SANKARAKUMARAN (International Journal of Pharma and Bio Sciences, 2017)
The objective of this study is to compare the effect of traditional and integrated pelvic floor exercise regimes for treating pelvic floor dysfunction in women. Using convenient sampling method, based on inclusion and exclusion criteria 30 subjects were selected for the study and they were allocated into two groups. The researcher was blinded for subject allocation and outcome measure.The symptoms, quality of life and pelvic floor muscle strength was assessed using PFD-Q and pelvexiser. The pelvic floor exercise with different regimes had been taught for both the groups respectively. Every 30 days the patient was asked to come for treatment progression based on muscle power evaluation the treatment protocol was changed. After the period of 90 days the post-test values was measured using PFD-Q and pelvexiser. The collected data were tabulated and analyzed using descriptive and inferential statistics This study showed statistically significant improvement in the quality of life and reduction in the pelvic floor dysfunction symptoms (P<0.001) and improvement in pelvic floor muscle strength (P<0.001) in group-B treated with integrated pelvic floor exercise compared to group-A treated with traditional pelvic floor exercise. From this study it is concluded that the integrated pelvic floor exercises helps in strengthening the pelvic floor and reduce the symptoms. This can be incorporated in clinical practice for better results.